PENGEMBANGAN MEDIA PEMBELAJARAN POWERPOINT INTERAKTIF PADA MATERI PESAWAT SEDERHANA UNTUK PESERTA DIDIK KELAS VIII SMPN 5 JOMBANG - Mochammad Asroru Pahala; Nur Kuswanti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The learning media plays an important role in the learning process. Proper selection of media learning can increase the motivation and understanding of pesera learners in the process of learning teaching. The mainstream media is a powerpoint medium that can display text, pictures, and animated videos. However, the senior high school media is still on the chalkboard. Thus, asa solution to the problem researchers developed interactive, powerpoint learning media on simple aircraft matter viii. The study follows the development of addie through analysis (analysis), design (design), development (development), implementation (application), and evaluation (application). It aims to produce a worthy learning medium on the basis of validity, practicality, and effectiveness. The results of this study are stated to be perfectly valid by the validator with an average score of 3.61. Practical test results came from the educational response sheet with an average score of 95% of the most practical criteria. Then the effectiveness of interactive powerbased teaching media is categorized highly effective with an average score of 87.5%. From these results it may conclude that the interactive powerpoint learning media is declared to be very valid, very practical, very effective, and worthy of use as learning media.